2021
DOI: 10.1155/2021/6629531
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Magnesium Salt Attenuates Lipopolysaccharide-Induced Acute Lung Injury via Inhibiting of TLR4/NF-κB Signaling Pathway

Abstract: Baicalin (BA) magnesium salt (BA-Mg) is a good water-soluble ingredient extracted from Scutellaria baicalensis Georgi, a commonly used traditional Chinese medicine. This study is aimed at investigating whether BA-Mg could exert a better protective effect on lipopolysaccharide- (LPS-) induced acute lung injury (ALI) in mice and illuminate the underlying mechanisms in vivo and in vitro. Mice were intraperitoneally administrated with equimolar BA-Mg, BA, and MgSO4 before LPS inducing ALI. Lung tissues and broncho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Baicalin inhibits the release of HMGB1 and cytokines from macrophages, improves survival and reduces tissue injury in septic mice induced by lipopolysaccharide (LPS) ( Wang and Liu, 2014 ). By inhibiting TLR4, baicalin has a therapeutic impact on LPS-induced ALI ( Huang et al, 2008 ; Shin et al, 2015 ) as well as acute pancreatitis-associated lung injury ( Zhang et al, 2008 ; Li et al, 2009a ; Zhang et al, 2021d ). Ding et al (2016) explained the crosstalk between the C-X3-C motif chemokine ligand 1 (CX3CL1)- C-X3-C motif chemokine receptor 1 (CX3CR1) axis and NF-κB pathway, while Meng et al revealed that oxidative stress and inflammation were reduced via the activation of the nuclear factor erythroid 2-related factor 2 (NRF2)-mediated heme oxygenase 1 (HO-1) signaling pathway ( Meng et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Baicalin inhibits the release of HMGB1 and cytokines from macrophages, improves survival and reduces tissue injury in septic mice induced by lipopolysaccharide (LPS) ( Wang and Liu, 2014 ). By inhibiting TLR4, baicalin has a therapeutic impact on LPS-induced ALI ( Huang et al, 2008 ; Shin et al, 2015 ) as well as acute pancreatitis-associated lung injury ( Zhang et al, 2008 ; Li et al, 2009a ; Zhang et al, 2021d ). Ding et al (2016) explained the crosstalk between the C-X3-C motif chemokine ligand 1 (CX3CL1)- C-X3-C motif chemokine receptor 1 (CX3CR1) axis and NF-κB pathway, while Meng et al revealed that oxidative stress and inflammation were reduced via the activation of the nuclear factor erythroid 2-related factor 2 (NRF2)-mediated heme oxygenase 1 (HO-1) signaling pathway ( Meng et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The role of magnesium during the inflammatory response was described more than twenty years ago in an LPS-induced sepsis model in rats with a deficient magnesium diet, showing a hyperinflammatory state and increased mortality [248]. In vitro, it has been reported that magnesium decreases the expression of IL-6 and TNF-α in LPS-stimulated monocytes; moreover, in acute lung injury in mice, magnesium treatment increases antioxidant response and reduces inflammatory cytokines through NF-kB inhibition [249]. Although the exact mechanism is not fully understood yet, one possible mechanism may be the antagonism between magnesium and calcium, as calcium depletion has been shown to replicate the anti-inflammatory effects of magnesium in vitro and in vivo [250,251].…”
Section: Functions In the Inflammatory Responsementioning
confidence: 99%